CCNP and CCIE Collaboration Core CLCOR 350-801 Official Cert Guide - Ball, Jason (Cisco Press, 2020)
CCNP and CCIE Collaboration Core CLCOR 350-801 Official Cert Guide is Cisco's official, comprehensive self-study resource for Cisco's CLCOR 350-801 exam (Implementing Cisco Collaboration Core Technologies), part of today's pathway to the CCNP Collaboration credential. It will thoroughly prepare network professionals to install, configure, support, and troubleshoot today's Cisco Collaboration endpoint and infrastructure products in modern on-premises environments. Designed for all CCNP Collaboration candidates, it covers every CLCOR 350-801 exam objective concisely and logically, with extensive teaching features designed to promote retention and understanding. You'll find: Pre-chapter quizzes to assess knowledge upfront and focus your study more efficiently Foundation topics sections that explain concepts and configurations, and link theory to practice Key topics sections calling attention to every figure, table, and list you must know Exam Preparation sections with additional chapter review features Final preparation chapter providing tools and a complete final study plan A customizable practice test library This guide offers comprehensive, up-to-date coverage of all CLCOR 350-801 exam topics related to: Audio and video fundamentals The Cisco UC phone and telepresence endpoint product portfolio Network requirements to support on-premises collaboration deployments Infrastructure components, from call control through Cisco Unified Communications Manager Edge products available in Cisco collaboration solutions Cisco Unity Connection and Cisco's Instant Messaging (IM) and presence services Maintenance, support, and troubleshooting for Cisco Collaboration systems and components.
Online resource; Title from title page (viewed May 13, 2020)